Persistent Threat of Lassa Fever in Nigeria: Epidemiology, Challenges, and Strategies for Effective Management - Akafa, Tensaba Andes; John, Artu Ishishen; Oladele, Gloria Omonefe; Umaru, Isaac John (Darul Yasin Al Sys, 2025)
Lassa fever is a viral hemorrhagic disease that poses a significant public health threat in Nigeria and West Africa. This review assesses the epidemiological trends, health impacts, and socioeconomic consequences of Lassa fever in Nigeria while proposing strategies for effective management and prevention. The natural reservoir of the Lassa virus, the multimammate rat (Mastomys natalensis), is prevalent in Nigerian households, facilitating transmission through direct contact with the rodents or their excreta, which often contaminates food. Consumption of these rats as a delicacy further exacerbates the risk. Current epidemiological data reveal that Lassa fever is endemic in Nigeria, with seasonal outbreaks primarily occurring in the dry season. The Nigeria Centre for Disease Control and Prevention (NCDC) reported 80 deaths and 413 confirmed cases across 11 states during Epidemiological Week 6 of 2025, with Taraba, Ondo, Bauchi, and Edo states accounting for over 73% of these cases. The Case Fatality Rate (CFR) for Lassa fever has risen to 19.4% in 2025, compared to 17.5% in 2024, likely due to factors such as underreporting and limited healthcare access. Notably, the CFR can range from 1% to 50%, influenced by healthcare access and early detection. The urgent nature of Lassa fever necessitates enhanced public health interventions, community education, and effective surveillance systems to mitigate its incidence and socioeconomic impact in Nigeria, thereby contributing to the achievement of Sustainable Development Goal target 3.3 to eliminate epidemics of Lassa fever and other neglected tropical diseases by 2030.